Architectural characteristics of dominant leg muscles in junior soccer players - Kearns, C. F.; Isokawa, M.; Abe, T. (European Journal of Applied Physiology, 2001)
The preferential use of dominant over non-dominant limbs produces muscle hypertrophy in the dominant limb. The purpose of this study was to investigate the architectural characteristics of the muscle that are associated with dominant leg use in junior soccer players. Fascicle length, pennation angle and muscle thickness of the medial gastrocnemius (MG) were measured by B-mode ultrasound in 26 junior soccer players [mean (SD) age: 16.5 (0.6) years] and 20 control college students [age: 18.5 (0.5) years]. Lower leg circumference and MG muscle thickness were significantly (P<0.05) greater in the soccer players than in the controls. The percent difference (dominant minus non-dominant legs) in muscle thickness and fascicle length were significantly (P<0.01) larger in the soccer players than in the controls, but the percent difference in pennation angle was similar between groups. The difference (dominant leg minus non-dominant leg) in muscle thickness was significantly correlated (r=0.55; P<0.05) with the difference in muscle fascicle length in the soccer players, but not in the controls (r=0.18). In conclusion, the preferential use of one limb over another, as seen in junior soccer players, results in a greater difference in muscle thickness between the dominant and non-dominant legs. This difference in muscle size was associated with longer fascicle lengths of the dominant leg. Thus, it appears possible that fascicle length may be further influenced by physical training in dominant legs.